Harmonisasi Filsafat Dengan Agama dalam Risalah al-Ḥilah Li Daf‘ al-Aḥzān Karya Al-Kindi - Ahmad Fadhil (Aqlania, 2022)
This paper aims, firstly, to present a complete translation of the Risa>lah al-H}i>lah li Daf‘ al-Ah}za>n into Indonesian, and secondly, to suggest that al-Kindi has paved the way for the harmonization between religion with philosophy. Conducting research on al-Kindi’s philosophy is important because some Islamic Philosophy scholars almost ignored him and jumped into Ibnu Rusyd's book Fas}l al-Maqa>l as the major resource in this discourse. This paper uses a library research methodology. The translation of Risalah al-H}ilah li Daf‘ al-Ah}zan in this paper referred to the publication of this treatise edited by ‘Abd al-Rahman Badawi. This paper concludes that there are indicators of the influence of Stoicism, Socrates, and Aristotle in al-Kindi’s Risalah al-H}ilah li Daf‘ al-Ah}zan and has many relevancies with principles of Rational, Emotional, Behavioral Therapy (REBT). But, al-Kindi’s rational method of dealing with grief is also in line with the guidance of the Qur’an.